The safety and clinical outcomes of endovascular treatment versus microsurgical clipping of ruptured anterior communicating artery aneurysms: a 2-year follow-up, multicenter, observational study - Yang, Minghao; Li, Yang; Li, Jia; An, Xiuhu; Li, Hongwen; Wang, Bangyue; Zhao, Yan; Zhu, Xiaowei; Hou, Changkai; Huan, Linchun; Yang, Xinyu; Yu, Jianjun (Frontiers in Neurology, 2024)
Background and objective: Current data on the optimal treatment modality for ruptured anterior communicating artery (AComA) aneurysms are limited. We conducted this multicenter retrospective study to evaluate the safety and clinical outcomes of endovascular treatment (EVT) and microsurgical clipping (MC) for the treatment of ruptured AComA patients.Methods: Patients with ruptured AComA aneurysms were screened from the Chinese Multicenter Cerebral Aneurysm Database. Propensity score matching (PSM) was used to adjust for baseline characteristic imbalances between the EVT and MC groups. The safety outcomes included total procedural complications, procedure-related morbidity/death and remedial procedure for complication. The primary clinical outcome was 2-year functional independence measured by the modified Rankin scale (mRS) score.The analysis included 893 patients with ruptured AComA aneurysms (EVT: 549; MC: 346). PSM yielded 275 pairs of patients in the EVT and MC cohorts for comparison. Decompressive craniectomy being more prevalent in the MC group (19.3% vs. 1.5%, P < 0.001). Safety data revealed a lower rate of total procedural complications (odds ratio [OR] = 0.62, 95% CI 0.39-0.99; P = 0.044) in the EVT group and similar rates of procedure-related morbidity/death (OR = 0.91, 95% CI 0.48-1.73; P = 0.880) and remedial procedure for complication (OR = 1.35, 95% CI 0.51-3.69, P = 0.657) between the groups. Compared with that of MC patients, EVT patients had a greater likelihood of functional independence (mRS score 0-2) at discharge (OR = 1.68, 95% CI 1.14-2.50; P = 0.008) and at 2 years (OR = 1.89, 95% CI 1.20-3.00; P = 0.005), a lower incidence of 2-year allcause mortality (OR = 0.54, 95% CI 0.31-0.93; P=0.023) and a similar rate of retreatment (OR = 1.00, 95% CI 0.23-4.40; P = 1.000).Conclusions: Clinical outcomes after treatment for ruptured AComA aneurysms appear to be superior to those after treatment with MC, with fewer overall procedure-related complications and no increase in the retreatment rate. Additional studies in other countries are needed to verify these findings.